Análise do grau de maturidade em Gestão Do Conhecimento na Universidade do Estado do Amazonas - Galves, Jeane Macelino (2022)
This dissertation addresses Knowledge Management (KM) in a public Higher Education Institution, with a predominantly bureaucratic organizational structure. In public universities, administrative activities are based on the knowledge and guidelines of the rules, norms and legislation determined by the Public Administration. Therefore, it becomes relevant for the public organization to insert strategic KM actions in line with its strategic objectives. This will allow the identification, creation, storage, application and sharing of knowledge (critical and organizational) that will result in the quality of the services provided and in greater social effectiveness. Thus, a methodological procedure was designed based on a descriptive case study with a quantitative and predominantly qualitative approach. Data collection included the application of semistructured interviews and a questionnaire with 42 objective assertions based on the Instrument for Assessing KM in Public Administration, proposed by Batista (2012), in the MGCAP Maturity Model. The research result shows that the degree of maturity of the studied institution is of initiation, as proposed by APO (2020), a level at which the organization begins to understand, understand and recognize the importance of managing knowledge. In addition, some practices are pointed out, aiming at raising the organizational level, and work suggestions are made for the gaps found.